A new species of eastern Nearctic Isoperla from Alabama and Mississippi, U.S.A. (Plecoptera: Perlodidae; Isoperlinae) - Grubbs, Scott A. (Illiesia, 2010)
Isoperla jamesae sp. n. (Perlodidae: Isoperlinae) is described from northwestern Alabama and northeastern Mississippi, U.S.A. Detailed descriptions of the adult male and female are supported by line drawings. Scanning electron micrographs are used to illustrate details of the male aedeagus and egg.
Keywords: entomologija; entomology; new species; vrbnice; nove vrste; Plecoptera; Isoperlinae; Isoperla; Alabama; Mississippi; USA